THE EFFECT OF USING VIDEO LEARNING MEDIA ON STUDENTS’ ACADEMIC RESULT OF CLASS XI TBSM-B FOR SUBJECT OF MOTORCYCLE INJECTION FUEL SYSTEM IN SMKN-1 KAHAYAN HILIR IN ACADEMIC YEAR 2017/2018 - Jepri Indra Alfianto (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2020)
T This study aims to determine the influence of implementation of video learning media on the subject of motorcycle injection fuel systemtaught in class XI with vocational concentration is Motorcycle Business Engineering at SMK 1 Kahayan Hilir. The research is based on True Experimental Design by the Pretest - Postest type for Control Group Design. The study uses population of whole students in class XI TBSM as many as 38, in which the class XI TBSM-A is as a Control class with a total sample at about 18 participants using image media. Meanwhile Class XI TBSM-B becomes an experimental class target with a total sampleat around 20 students for video media model. Data collection is obtained from the pre-test and post-test sheet. Learning students’ result of Test Instrument (THB) contributes as the research instrument which is using the form of Multiple Choice Based on the results of pre-test data analysis, the average value of the experimental class reaches 59.60 while the control class provides 60 point. In the post-test, the experimental class gives 75.95 subsequently the control class is about 69.17. Therefore, the average of experimental class and control class show 5% in significant level by obtained the prices for ttable and t are respectively 2.028 and 5.55. Then, results depicts that there is 5.55 > 2,028. Thus it can be concluded that there is the influence of the use of video learning media on the learning students’ results of Class XI for the subject of motorbike fuel injection systems. This results informs us that the average value of experimental class for post-test is higher than the results of the average value for control class. As the consequent, the use of video media can contribute as the learning model to help the learning process in improving of students’ learning progress.